Kesultanan Kualuh Desa Tanjung Pasir Kabupaten Labuhanbatu Utara: Sejarah dan Peran Sosial Budayanya, 1829 – 1937 - Lestari, Ayu; Monang, Sori; Nurhayani, Nurhayani (Medan Resource Center, 2025)
This study aims to examine the historical trajectory and socio-cultural influence of the Kualuh Sultanate in Tanjung Pasir Village, North Labuhanbatu Regency, during the period of 1829–1937. Employing a historical method within a social history framework, the research draws on data collected through interviews, direct observations, and analysis of both primary and secondary sources. The findings reveal that the Kualuh Sultanate had a significant historical connection with the Sultanate of Asahan and played a crucial role in the spread of Islam, the construction of religious institutions such as mosques, and the formation of local identity among the surrounding communities. One of the most prominent legacies is the Grand Mosque of Alhadji Muhammad Syah, which serves as a lasting symbol of the sultanate's cultural and religious influence. This research underscores the importance of preserving local historical heritage and highlights its contribution to a broader understanding of regional history in North Sumatra.